IS IT PURIM YET? - Barash, Chris; Psacharopulo, Alessandra (New York, NY : AV2 by Weigl, 2019)
"As winter winds down and springtime seems like it's still a dream away, a family begins preparations for Purim. It's time to fill hamantaschen, swing groggers, and gather together. Whether dressed as a queen or in a Mordecai crown, let's celebrate how Queen Esther's bravery protected the Jews!"--Jacket.
First published in 2016 by Albert Whitman & Company
Keywords: Purim -- Juvenile fiction; Fasts and feasts -- Judaism -- Juvenile fiction; Families -- Juvenile fiction; Stories in rhyme